(untitled) (Brazilian Journal of Radiation Sciences, 2025)
This study estimated the ambient equivalent dose rate in the oil parish of Pacayacu, which is located in Lago Agrio, Sucumbíos province. It has experienced constant oil activity since 1980. Measurements were performed in 77 different places, including 63 closed oil wells, eight points near operating wells, three points between Pacayacu and the Aguarico River, one mining concession, and two control points. Ludlum digital meters connected to NaI(Tl) scintillation probes were used to obtain five one-minute measurements at each site. The average ambient equivalent dose rate was 0.12 µSv·hˉ¹, with values ranging from 0.05 to 0.20 µSv·hˉ¹, excluding the highest value of 0.86 µSv·hˉ¹ at one site. The annual effective dose of the external irradiation was calculated using the average ambient equivalent dose rate at each sampling point. One closed well coded "PPC(SHR-04)" had an annual effective dose of 1.51 mSv·yˉ¹, that exceeded the public exposure limit established by national law (0.3 mSv·yˉ¹) and the 1 mSv·yˉ¹ limit defined by the IAEA. Sweeping measurements around this well indicated that the elevated gamma radiation originated from pipes delimiting the well, point to the presence of NORM internal scales. Consequently, these results highlight the potential influence of oil activity on the annual effective dose. In oil areas, the focus should be on the importance of proper waste management to prevent exposure to NORM, avoid internal contamination and environmental pollution.